2021
DOI: 10.1111/1742-6723.13839
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Drugs Network of Australia: A toxicosurveillance system of illicit and emerging drugs in the emergency department

Abstract: Objective: The unprecedented rise in synthetic drugs, many containing unknown toxic agents, has made timely analytical diagnosis more difficult, and has reduced the confidence of clinicians providing ED management to this population of patients. This has also impacted the quality of evidence informing harm reduction responses. The Emerging Drugs Network of Australia (EDNA) brings together emergency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…After reviewing this cluster of deaths from 2016 to 2017, the Coroners Court of Victoria (2021) recommended the urgent implementation of both a DCS and an early warning network. In response, the Victorian Government began releasing public drug alerts and now funds part of the Emerging Drugs Network of Australia (Smith et al , 2022). Despite these welcome advances, there is still no public access to substance analysis.…”
Section: Discussionmentioning
confidence: 99%
“…After reviewing this cluster of deaths from 2016 to 2017, the Coroners Court of Victoria (2021) recommended the urgent implementation of both a DCS and an early warning network. In response, the Victorian Government began releasing public drug alerts and now funds part of the Emerging Drugs Network of Australia (Smith et al , 2022). Despite these welcome advances, there is still no public access to substance analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies, nationally [26,27] and internationally [28][29][30], have reported the benefits of analytically confirmed drug data from ED populations to enable detection of specific compounds and their associated toxicity. A key advantage for frontline clinicians is improved access to timely and objective clinical and toxicological information [31]; a recognised gap in current clinical practice and medical curricula [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Drug-use is generally self-reported in clinical, community, and research settings. For example, hospital data is coded on clinical observations and inferences about the drugs involved and systems are generally insensitive to capturing novel and emerging substances of concern (52). Under-reporting of substance use in acute settings may underestimate the burden of drug-related harms, impacting capacity for planning and provision of best-practice policies, prevention, and care (1,28,33,34).…”
Section: Alert Dissemination Andmentioning
confidence: 99%
“…Under-reporting of substance use in acute settings may underestimate the burden of drug-related harms, impacting capacity for planning and provision of best-practice policies, prevention, and care (1,28,33,34). When blood samples are routinely collected in severe or unusual toxicity presentations, toxicosurveillance can screen for substances and ndings can be translated into timely and appropriate clinical responses and/or used to inform EWS and public health risk communications (16,52,79). For example, in Victoria, EDNAV reported in 2021, that 90% of 320 acute presentations screened for illegal, pharmaceutical, and novel substances, one or more substances unknown to the clinical team at time of management were detected.…”
Section: Alert Dissemination Andmentioning
confidence: 99%
See 1 more Smart Citation